Bond graph modelling of a wastewater biodegradation bioprocess - Roman, M.; Selisteanu, D.; Bobasu, E.; Petre, E.; Sendrescu, D. (2009 IEEE International Conference on Automation and Logistics, 2009)
This paper addresses the problem of Bond Graph modelling of nonlinear bioprocesses. The rules for the design of pseudo Bond Graph models of some prototype bioprocesses - one batch and one continuous process - are obtained using the reaction schemes and the analysis of biochemical phenomena. These rules are applied in order to design the Bond Graph model of a complex wastewater treatment process, which is a biomethanation process - bio-degradation with production of methane gas. This bioprocess takes place into a Continuous Stirred Tank Bioreactor. The obtained Bond Graph models and several simulations are conducted using 20sim modelling and simulation environment. This modelling procedure represents a valuable illustration of the power of Bond Graph technique, and can be used as a base for the development of the models of bioprocesses with high level of complexity.